Isolation and Phylogenetic Analysis of Thermophile Community Within Tanjung Sakti Hot Spring, South Sumatera, Indonesia - Heni Yohandini; . Julinar; . Muharni (HAYATI Journal of Biosciences, 2015)
A community of thermophiles within Tanjung Sakti Hot Spring (South Sumatera) have been cultivated and identified based on 16S ribosomal RNA gene sequence. The hot spring has temperature 80C-91C and pH 7-8. We used a simple method for culturing the microbes, by enriching the spring water with nutrient broth media. Phylogenetic analysis showed that the method could recover microbes, which clustered within four distinct taxonomic groups: Anoxybacillus, Geobacillus, Brevibacillus, and Bacillus. These microbes closely related to Anoxybacillus rupiensis, Anoxybacillus flavithermus, Geobacillus pallidus, Brevibacillus thermoruber, Bacillus licheniformis, and Bacillus thermoamylovorans. The 16S ribosomal RNA gene sequence of one isolate only had 96% similarity with Brevibacillus sequence in GenBank.